Get the Science Right when Paying for Nature’s Services - Naeem, S.; Ingram, J.C.; Varga, A.; Agardy, T.; Barten, P.; Bennett, G.; Bloomgarden, E.; Bremer, L.; Burkill, P.; Cattau, M.; Ching, C.; Colby, M.; et al. (American Association for the Advancement of Science, 2015)
Few projects adequately address design and evaluation